Primary Presentation of Pulmonary Hypertension in the Peripartum: Preparing for Patients With Eisenmenger Physiology - Countouris, Malamo E. (JACC Case Rep, 2020)
A Bosnian woman at 20 weeks’ gestation presented with dyspnea and hypoxia. She was diagnosed with Eisenmenger physiology with severe pulmonary hypertension, ventricular septal defect, and patent ductus arteriosus. Given high maternal mortality, coordination of care with a multidisciplinary team approach may allow for best possible outcomes. (Level of Difficulty: Intermediate.)